2009
DOI: 10.1002/path.2608
|View full text |Cite
|
Sign up to set email alerts
|

RNA splicing factors regulated by HPV16 during cervical tumour progression

Abstract: The most prevalent human papillomaviruses (HPVs) causing cervical disease are the 'high-risk' HPV types 16 and 18. All papillomaviruses express a transcription factor, E2, that can regulate viral and cellular gene expression. Recently, we demonstrated high-risk HPV E2-mediated transcriptional transactivation of SF2/ASF. This essential oncoprotein is a key member of a family of proteins, the SR proteins, that regulate constitutive and alternative splicing. Tight control of RNA splicing is necessary for the prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
80
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 31 publications
7
80
0
1
Order By: Relevance
“…it was previously described that hpV proteins also regulate gene expression at the transcriptional level and affect splicing by the up-regulation of splicing factors. in fact, the hpV E2 protein acts as a transcription factor, not only in terms of viral gene regulation, but also by altering the expression of multiple cellular genes, including splicing factors Sr (arginine/serine-rich splicing factor protein family), splicing factor 2/alternative splicing factor (SF/aSF) and heterogeneous nuclear ribonucleoprotein a1 (hnRNPA1) (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…it was previously described that hpV proteins also regulate gene expression at the transcriptional level and affect splicing by the up-regulation of splicing factors. in fact, the hpV E2 protein acts as a transcription factor, not only in terms of viral gene regulation, but also by altering the expression of multiple cellular genes, including splicing factors Sr (arginine/serine-rich splicing factor protein family), splicing factor 2/alternative splicing factor (SF/aSF) and heterogeneous nuclear ribonucleoprotein a1 (hnRNPA1) (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we demonstrated that the three smallest SR proteins, SRSF1, SRSF2, and SRSF3, are overexpressed during cervical tumor progression (24), suggesting that they may possess cervical tumor-promoting activities. Figure 2 shows that these three proteins are overexpressed in W12t and W12ti tumor cells (lanes 3 and 4), compared to a much lower expression level in the W12E and W12G nontumor cells (lanes 1 and 2).…”
Section: Hpv16mentioning
confidence: 96%
“…Apart from RNA processing-related functions, SR proteins have also been shown to be involved in chromatin remodelling, transcriptional regulation, genome stability maintenance, nucleolar stress, cell cycle progression, apoptosis control, and protein sumoylation (15)(16)(17)(18)(19)(20). Unsurprisingly, due to their diverse functions, many SR proteins are overexpressed in a range of tumors (21)(22)(23)(24)(25). Importantly, SRSF1 (ASF/SF2), SRSF3 (SRp20), and SRSF9 (SRp30c) have been shown to possess oncogenic properties (22)(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
mentioning
confidence: 99%
See 2 more Smart Citations